2021
DOI: 10.1136/bmjopen-2020-041578
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of frailty among Chinese community-dwelling older adults with type 2 diabetes: a cross-sectional survey

Abstract: ObjectivesTo assess the prevalence of frailty and identify predictors of frailty among Chinese community-dwelling older adults with type 2 diabetes.DesignA cross-sectional design.SettingTwo community health centres in central China.Participants291 community-dwelling older adults aged ≥65 years with type 2 diabetes.Main outcome measuresData were collected via face-to-face interviews, anthropometric measurements, laboratory tests and community health files. The main outcome measure was frailty, as assessed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
2
14
0
2
Order By: Relevance
“…Comparison at baseline in this study showed that older adults, females, individuals with lower education levels, and widowed older adults were associated with a higher proportion of frailty and diabetes with frailty. Among older adults with diabetes and frailty, there was an increased proportion with 3 or more chronic diseases and multiple medications, a significant decrease in the activities of daily living and cognitive functions, and an increase in depression scores, all of which were consistent with previous studies ( 19 21 ). Therefore, targeted intervention would be desirable in the management of older adults with diabetes and frailty to delay the course of diseases, relieve harm resulting from comorbidities, reduce the risk of adverse outcomes, and improve the level of diabetes management overall.…”
Section: Discussionsupporting
confidence: 89%
“…Comparison at baseline in this study showed that older adults, females, individuals with lower education levels, and widowed older adults were associated with a higher proportion of frailty and diabetes with frailty. Among older adults with diabetes and frailty, there was an increased proportion with 3 or more chronic diseases and multiple medications, a significant decrease in the activities of daily living and cognitive functions, and an increase in depression scores, all of which were consistent with previous studies ( 19 21 ). Therefore, targeted intervention would be desirable in the management of older adults with diabetes and frailty to delay the course of diseases, relieve harm resulting from comorbidities, reduce the risk of adverse outcomes, and improve the level of diabetes management overall.…”
Section: Discussionsupporting
confidence: 89%
“…However, studies reporting an association of low glycaemia with frailty demonstrated common features of participants, which included lower body weight and malnutrition compared with non-frail patients, suggesting an AM phenotype [ 147 ]. On the other hand, other studies reporting an association of high glycaemia with frailty demonstrated common features of participants, which included higher body weight, higher waist circumference and higher cholesterol compared to non-frail patients, suggesting a SO phenotype [ 148 , 149 , 150 , 151 ]. The association of frailty with both low and high glycaemia can be explained by the presence of two metabolic rather than one phenotype of frailty, which needs future confirmation [ 152 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Approximately 1 in 6 community-dwelling people > 65 years old is frail [6], a percentage that increases with age. In elderly people with diabetes, the reported prevalence of prefrailty and frailty can be as high as 51.5% and 19.2%, respectively [7].…”
Section: Knowledge Transfer Of Dr Zoe Pafili (Athens)mentioning
confidence: 99%